2005
DOI: 10.1111/j.1365-2125.2005.02372.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of imatinib mesylate in patients with chronic‐phase chronic myeloid leukaemia: results of a phase III study

Abstract: AimsThis study was designed to investigate the biochemical and physiolog ical covariates or comedications that affect the pharmacokinetics of imatinib mesylate in patients with chronic-phase chronic myeloid leukaemia (CP CML). MethodsPharmacokinetic data were analyzed in 371 patients receiving 400 mg imatinib once daily during a phase III trial of imatinib vs interferon-alfa plus cytarabine for the treatment of newly diagnosed CP CML. Covariates included age, weight, sex, ethnicity, haemoglobin (Hb) concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
65
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 13 publications
18
65
1
1
Order By: Relevance
“…1). This model was previously used by Schmidli et al to analyze data from 371 patients (18). Moreover, alternative structural models (i.e., first-order absorption, two-compartment model) were not associated with a lower objective function value.…”
Section: Resultsmentioning
confidence: 99%
“…1). This model was previously used by Schmidli et al to analyze data from 371 patients (18). Moreover, alternative structural models (i.e., first-order absorption, two-compartment model) were not associated with a lower objective function value.…”
Section: Resultsmentioning
confidence: 99%
“…The pharmacokinetics of imatinib has been extensively studied in Caucasian CML patients [17][18][19][20][21] . However, few studies have been reported on naïve Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, population analysis of imatinib pharmacokinetics showed that ethnic effect was not significant. 17 Since imatinib exhibits dose proportionality from 25 to 1000 mg and it is reported that there is no difference in pharmacokinetics between healthy adults and patients, the results from the present study can be extrapolated to the targeted patients.…”
Section: Resultsmentioning
confidence: 90%